The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3390/su6128379
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Professionals’ Needs and Preferences for Sustainable Building Guidelines in Korea

Abstract: Abstract:The issue of sustainability has become one of the major concerns among architectural professionals throughout the world. As a way of providing information, many countries have developed and distributed sustainable building guidelines. This paper aims to investigate architectural professionals' needs and preferences with regard to sustainable building guidelines in Korea, with a specific focus on various guideline attributes. We conducted a review of existing sustainable building guidelines in many cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Studies have indicated that cities' carbon dioxide emissions account for 80% of the global total [3], and the energy OPEN ACCESS consumed by the building industry globally accounts for 40% of total energy consumption [4]. Therefore, when faced with rapid urbanization and attendant environmental change, governments and educators in various countries will likely devote increased attention to engaging in greener development [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that cities' carbon dioxide emissions account for 80% of the global total [3], and the energy OPEN ACCESS consumed by the building industry globally accounts for 40% of total energy consumption [4]. Therefore, when faced with rapid urbanization and attendant environmental change, governments and educators in various countries will likely devote increased attention to engaging in greener development [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is very important that the education in architecture is sufficiently strong, so that the students acquire skills and competencies to deal with the sustainability issues in the future [18][19][20][21][22][23][24][25].…”
Section: Architectural Design Methodsmentioning
confidence: 99%
“…The implementation of such strategies can be aided by a tool that can support architects in the implementation of sustainability principles during the architectural design process [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, Hook Han and Sook Kim investigated architectural professionals' needs and preferences with regard to sustainable building guidelines and they identified that an urgent demand consist on the commitment of providing "education on the significance of sustainable buildings and promote a better understanding of sustainable principles" and "comprehensive and detailed information on sustainable building design strategies and technologies" [42].…”
Section: Methodsmentioning
confidence: 99%
“…According to this extended research of Hook Han and Sook Kim [42], it is revealed that the building energy efficiency problem is entrapped to a complex network of sustainable building guidelines assortments. Furthermore, architects and building professionals do not manage to correctly figure out how they should apply these guidelines, since they do not apprehend the real nature of the problem and they just try to blindly fulfill requirements in order to deal with a physical problem with specific characteristics without understanding the physics beyond.…”
Section: Methodsmentioning
confidence: 99%